A Proposal Towards a VNS-Based Decision Support Tool for Large Scale Location-Covering-type Problems - Plastria, Frank (Yugoslav Journal of Operations Research; Vol 34 No 3 (2024), 2024)
We describe a number of typical features, constraints and objectives, frequently appearing in spatial system-design of maximum covering-type, such as emergency response systems. We then indicate some heuristic local search methods topped by a Variable Neighbourhood Search to construct and search for good solutions. These ideas were intended to form the basis for a possibly multi-objective spatial decision support system.